Stability and Efficacy of Live-Attenuated Vibrio harveyi Vaccines Under Different Storage Conditions in Zebrafish (Danio rerio) Models - Mohd Hafiz Ngoo Muhamad-Sofie; Aslah Mohamad; Mohamad Azzam-Sayuti; Mohammad Noor Azmai Amal; Mohd Zamri-Saad; Md Shirajum Monir; Ina Salwany Md Yasin (Jurnal Ilmiah Perikanan dan Kelautan)
Graphical Abstract